Natriuretic Peptides in Chronic Heart Failure - Hans-Peter Brunner-La Rocca; Sandra Sanders-van Wijk (Cardiac Failure Review)
Normal brain natriuretic peptide (BNP) and N-terminal proBNP (NT-proBNP) levels are helpful in excluding chronic heart failure in the ambulatory setting, although they have been studied less well and possibly less accurately than in acute care. They may also be of help in screening patients at risk to intervene and reduce the development of heart failure. Natriuretic peptides are also excellent prognostic markers of chronic heart failure, but the clinical value of such prognostic information is less clear. One possible application for this information is guiding medical therapy in chronic heart failure. Many studies have investigated this approach, but results are mixed and do not clearly show improvement in outcome. Still, it may be that in patients with reduced ejection fraction and few comorbidities, measuring NT-proBNP to uptitrate medication improves prognosis.